Endoscopic Ultrasound-Guided Drainage of Pelvic Fluid Collections with Lumen-Apposing Metal Stents - Marco Pereira; Ana Caldeira; Joana Barreiro; Mafalda Almeida; António Banhudo (GE: Portuguese Journal of Gastroenterology)
Introduction: A pelvic abscess is a potential life-threatening condition that should be managed conservatively whenever possible. Currently, computed tomography or ultrasound-guided percutaneous drainage is still the gold standard approach for pelvic fluid collections (PFCs) requiring intervention. More recently, endoscopic ultrasound (EUS) drainage using lumen-apposing metal stents (LAMSs) has been used off-label in PFCs with similar efficacy, a favorable safety profile, better quality of life, and generally a shorter duration of treatment when compared to the gold standard treatment. Methods: An observational retrospective analysis of 6 patients who underwent EUS-guided PFC drainage with LAMS at our institution was conducted. Records were reviewed to identify etiology, size of the collection, number of endoscopic procedures required until complete resolution, stent indwelling time, concomitant surgical or percutaneous associated procedures, successful removal and resolution. Results: The 6 patients included had an average age of 69 years old and 5 (83.3%) were male. The average size of the PFCs was 72.5 mm. All patients (100%) had successful drainage following LAMS placement, though 1 patient had an early recurrence. The mean stent indwelling time in our study was 6.7 days. An additional percutaneous or surgical drainage intervention was not required in any of the participants. Also, no adverse events related to the procedure were reported during the follow-up period. Conclusion: EUS-guided drainage of PFCs with LAMS is a safe and minimally invasive technique, which allows rapid PFC resolution, with no need for percutaneous or surgical drainage interventions.